Spatial changes in the use of Non Timber Forest Products in four villages of Viengkham District, Luang Prabang Province, Lao PDR - Thephavanh, M.; Ponkphady, S.; Boucard, A.; Boissiere, M.; Castella, J.C.; Basuki, I.; Mouaxeng-Cha, K.; Vongmany, O. (2011)
The spatial patterns of NTFPs collection was investigated in four villages (Muongmuay, Vangmat, Bouammi and Phadeng) of Viengkham district in Luang Prabang Province. The survey aimed at characterizing different NTFPs collection practices across (i) a gradient of accessibility, population pressure and ethnicity, and (ii) a diversity of agroecological contexts characterized by their topography, soil types and land use. Eight wild plants species: 1 hard wood (may mi), 2 bamboos (may hia & may hok) and 5 commercial NTFPs (incense bark - peuakmeuak, broomgrass - kheme, rattan - waii, cardamom - mak neng & paper murlberry - posaa) were selected for this study. The changes in NTFPs collection practices were assessed through community surveys, participatory mapping and ground checking. Land use, soil characteristics and topography are key characteristics taken into account by local farmers to identify suitable areas for collection of major NTFPs. Shifting cultivation land type is the most cited as collection area for the different species. This may reflect the preference of certain highly used species like peuakmeuak and broomgrass for open spaces and light. It could also be explained by the perception of the villagers who collect wild species preferably on their upland fields or on the way to their fields. Lastly, the presence of species like broomgrass is an indicator of land degradation under intensive practice of slash-and-burn systems (fallows length < 4 years). Most species are found in humid soils and riparian forests (i.e. along streams). The study of changes in NTFPs collection practices shows that local people are getting more interested in forest conservation as the overall forest quality is degrading in their village and wild resources are depleted. On the other hand, the use of forest resources for timber and firewood are expected to decrease in the future. These changes in the relative importance of forest resources for villagers need to be further incorporated in biodiversity monitoring schemes and land use planning processes.